LEADERSHIP AND SUPERVISION OF ISLAMIC EDUCATION IN STRENGTHENING QUALITY MANAGEMENT AND HUMAN RESOURCES IN ISLAMIC EDUCATIONAL INSTITUTIONS - Hodiqotul Atfaliyah; Yosie Kristin Pandriyani; Zakaria Syafei; Eka Sri Mulyani; Rijal Firdaos (Cakrawala Pedagogik, 2026)
Educational leadership and supervision play a crucial role in improving the quality of management of Islamic educational institutions. Effective leadership not only directs the organization but also develops human resources and ensures optimal quality management. This study aims to analyze the role of leadership and supervision in strengthening quality management and human resource development. The method used is a qualitative approach through literature study with data sources from books, journals, and policy documents. Analysis is carried out through data reduction, categorization, interpretation, and drawing conclusions. The results show that effective Islamic educational leadership is visionary, participatory, and based on spiritual values. Systematic supervision can improve educator competence and build a culture of quality. In addition, the quality of human resources is crucial for the success of quality management. The integration of transformational leadership, ongoing supervision, and human resource development is a key strategy in improving the quality and competitiveness of Islamic educational institutions in the era of globalization.